Analisis Tingkat Kemampuan Pemecahan Masalah Getaran Harmonis Melalui Model Pembelajaran Perubahan Konseptual - Siti Zaenab; Muh. Makhrus; I Wayan Gunada (Department of Physics Education, Universitas Mataram, 2019)
The study aims to analyze the problem-solving ability (PSA) of students during the learning process with conceptual change learning model. This research is included in quantitative descriptive research with three experimental classes. PSA at the time of learning is measured by an assessment instrument that refers to the problems in the LKPD and PSA evaluation sheet which contains two description questions at every meeting for four meetings. The assessment instrument refers to four PSA indicators, namely the ability to understand problems, plan solutions, carry out problem-solving, and check again, which is done during the learning process. Data analysis of PSA research results based on LKPD found that 58% of students have PSA in the very good category and 42% in the good category, while based on the evaluation results at each meeting it was found that 27% in the very good category, 62% in the good category, and 11% in the medium category. Analysis of research data shows that the conceptual change learning model is good to improve the problem-solving ability of harmonic motion of students of SMAN 8 Mataram.